Are there different patterns of detrusor overactivity which are clinically relevant? ICI‐RS 2018. (10th December 2019) - Gajewski, Jerzy B.; Gammie, Andrew; Speich, John; Kirschner‐Hermanns, Ruth; De Wachter, Stefan; Schurch, Brigitte; Korstanje, Cees; Valentini, Francoise; Rahnama'i, Mohammad Sajjad
Abstract: Introduction: Different patterns of detrusor overactivity (DO) have been described and included in several standardization terminology documents. However, it is unclear if these different patterns have any clinical significance. Methods: This is a report of the proceedings of Proposal 3: "Are there different patterns of detrusor overactivity which are clinically relevant?" from the annual International Consultation on Incontinence—Research Society (ICIRS) meeting, which took place from 14 to 16 June 2018, in Bristol, UK. Results: We have collected and discussed, as a committee, the evidence about different urodynamic (UD) patterns of detrusor overactivity and their potential clinical significance. We reviewed the important previous basic research and clinical studies and compiled summaries. The discussion focused on clinical relevance of different UD patterns of DO and what further research is required. Conclusions: There are several UD definitions of patterns of detrusor overactivity, however the clinical relevance of these definitions remains unclear. Future research should concentrate on defining the pattern of DO in relation to clinical diagnosis, gender, age, and treatment outcomes.